The COVID-19 pandemic impact on health, social, and finances in clinical nutrition practitioners of Latin-American: An international survey - Díaz, Gustavo; Vedrenne-Gutiérrez, Fernand; García-Rairán, Luis; Fuchs-Tarlovsky, Vanessa (Perspectivas en Nutrición Humana, 2025)
Background & aim: Between July and November 2021, the Latin American region affronted the fourth COVID wave. The impact of the pandemic on health, social, and finances among nutrition practitioners is unknown. This study aimed to explore and describe the effects of the COVID-19 pandemic on the health, social, and finances wellbeing of Latin-American clinical nutrition practitioners. Methods: A international cross-sectional survey study was carried out. A 70-item web survey was self-completed by the nutrition community in 18 Latin American countries, including physicians, nutritionists, and nurses. Variable measured involve self-perception of repercussions on health, social, and finances wellbeing. Participated 398 health professionals including 63.1% dietitians/nutritionists, 25% physicians, and 12.1% nurses. Results: Median age was 37 years and 78.6% were female. The median of the COVID-19 care experiences was 12 months. Participants noted negative pandemic effects on health (85%), family/social life (82.7%), and personal finances (63.6%). Shortage of staff, equipment deficiency, and limited work experience correlated (p<0.05) with adverse impacts on health, social life, and finances. Conclusions: The impact of COVID-19 on nutrition practitioners in Latin America is a pressing issue that demands targeted support. We must ensure their health, social well-being, and financial stability to foster resilience and improve nutrition services and public health readiness for future pandemics.